Acute metformin treatment provides cardioprotection via improved mitochondrial function in cardiac ischemia / reperfusion injury - Siripong Palee (2020)
© 2020 The Author(s) Cardiac ischemia/reperfusion (I/R) injury following reperfusion therapy in acute myocardial infarction results in mitochondrial dynamic imbalance and cardiomyocyte apoptosis. Although diabetic patients taking metformin have been shown to have a lower risk of myocardial infarction, the efficacy of the cardioprotection conferred by metformin regarding the mitochondrial function and dynamic in cardiac I/R injury are still inconclusive. In addition, the comparative effects between different doses of metformin given acutely prior to cardiac I/R injury have never been investigated. Fifty 8-week-old male Wistar rats weighing 300−350 g were divided into sham-operated (n = 10) and cardiac I/R-operated (n = 40) groups. In the cardiac I/R group, rats underwent 30-min ischemia followed by 120-min reperfusion and were randomly divided into four subgroups (n = 10/group): control (received normal saline), metformin (100, 200, and 400 mg/kg). The arrhythmia score, cardiac function, infarct size, mortality rate, mitochondrial function and apoptosis, were determined. Metformin (200 mg/kg) exerted the highest level of cardioprotection through reduction in arrhythmia, infarct size, mitochondrial fission, and apoptosis, in addition to preservation of mitochondrial function, leading to the attenuation of cardiac dysfunction. Doses of metformin (100 and 400 mg/kg) also improved mitochondrial and cardiac function, but to a lesser extent than metformin (200 mg/kg). In conclusion, metformin exerts cardioprotection by attenuating mitochondrial dysfunction, mitochondrial dynamic imbalance, and apoptosis. These led to decreased infarct size and eventual improvement in cardiac function in rats with acute cardiac I/R injury. These findings indicate the potential clinical benefits of acute metformin treatment in acute myocardial infarction.